2020
DOI: 10.1016/j.lungcan.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Gene signatures of tumor inflammation and epithelial-to-mesenchymal transition (EMT) predict responses to immune checkpoint blockade in lung cancer with high accuracy

Abstract: Treatment of non-small cell lung cancer (NSCLC) with immune checkpoint blockade (ICB) has resulted in striking clinical responses, but only in a subset of patients. The goal of this study was to evaluate transcriptional signatures previously reported in the literature in an independent cohort of NSCLC patients receiving ICB. Materials and methods: This retrospective study analyzed transcriptional profiles from pre-treatment tumor samples of 52 chemotherapy-refractory advanced NSCLC patients treated with anti-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 51 publications
(71 reference statements)
1
98
0
Order By: Relevance
“…We do have some data to suggest that our APMS is not simply another surrogate for certain type of leukocyte infiltration. First, in our previous study using these same samples 12 (Supplemental figures 2 and 4), we saw no associations of response to anti-PD1 therapy with lymphocyte genes (CD4, CD8A, and CD8B), with macrophage genes (CD68, CD14, CD163, and CSF1R), or to fibroblast genes (ACTA2 and Col4A1). We saw no correlation between the APM score and expression levels of the genes for CD45, CD8A, CD11b, CD68, CD14, and CD163 (online supplemental figure 2).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We do have some data to suggest that our APMS is not simply another surrogate for certain type of leukocyte infiltration. First, in our previous study using these same samples 12 (Supplemental figures 2 and 4), we saw no associations of response to anti-PD1 therapy with lymphocyte genes (CD4, CD8A, and CD8B), with macrophage genes (CD68, CD14, CD163, and CSF1R), or to fibroblast genes (ACTA2 and Col4A1). We saw no correlation between the APM score and expression levels of the genes for CD45, CD8A, CD11b, CD68, CD14, and CD163 (online supplemental figure 2).…”
Section: Discussionmentioning
confidence: 73%
“…9 10 We previously showed that such an inflammatory gene signature was significantly associated with response to checkpoint blockade in patients with metastatic lung cancer with an AUC of 0.70 (figure 3A, gray line). 12 In the same NSCLC cohort, the eight-gene antigen processing score demonstrated an improved ability to predict response to checkpoint blockade relative to the inflammatory gene signature with an AUC of 0.84 (figure 3A, green line), even though there was a significant correlation between the APM score and inflammatory gene signature (Pearson's r=0.58, p<0.0001) ( figure 3B).…”
Section: Patient Characteristics and Responsesmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, these findings may suggest that cisplatin-resistant EMT tumor cells could display an increased sensitivity to anti-PD-1 or anti-PD-L1 antibody treatment [82]. However, recent studies investigating gene expression signatures, predicting the efficacy of PD-1/PD-L1 inhibitors in different cancer types, found that tumors with EMT or the mesenchymal phenotype showed a lower response rate [83][84][85]. Besides the potential application of the evaluation of the EMT status as a predictive marker for checkpoint agents, these results suggest that therapies aiming at the reversal of the EMT process may potentiate the efficacy of this type of cancer immunotherapy [86,87].…”
Section: Interaction With An Inflammatory Microenvironmentmentioning
confidence: 99%
“…A prognostic signature based on 11 immune-related genes (IRGs) for predicting CC (cervical cancer) patients' response to immune checkpoint inhibitors (ICIs) 28 LRRC15.CAF.Sig A signature of 14 marker genes of a specific type of carcinoma-associated fibroblasts (CAF) -"LRRC15 + CAFs" that correlated with poor response to anti-PD-L1 therapy 29 T.cell.inflamed.Sig An 18 gene "T-cell-inflamed gene expression signature" that can predict clinical benefit of anti-PD-1 in various cancer types (melanoma, head and neck squamous cell carcinomas, digestive cancers, ovarian and triple negative breast cancers) 24,30 IPRES.Sig IPRES (innate anti-PD-1 resistance) that included 16 genes involved in cell adhesion, extracellular matrix remodeling, angiogenesis, wound healing, and mesenchymal transition that predicted response to anti-PD-1 antibody therapy in melanoma 9,31 Inflammatory.Sig A gene expression signature of 27 inflammation related genes that predicted response to immune checkpoint blockade in lung cancer 31…”
Section: Irgsigmentioning
confidence: 99%